2021
DOI: 10.7150/jca.47883
|View full text |Cite
|
Sign up to set email alerts
|

Loss of LIMCH1 predicts poor prognosis in patients with surgically resected Lung Adenocarcinoma: A study based on Immunohistochemical Analysis and Bioinformatics

Abstract: Background: LIMCH1, a novel actin-binding protein, is reported to correlate with tumorigenesis in multiple cancer types, but its clinical prognostic value in lung adenocarcinoma (LUAD) patients remains unclear. Methods: A total of 196 patients with LUAD who underwent R0 resection were included for analysis. We integrated immunohistochemistry (IHC) and data mining analyses to determine LIMCH1 expression in tumor specimens; the chi-square test was used to explore the correlation between clinicopathologic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It is also shown that LIMCH1 protein is a transcription factor that promotes the expression of p53 LIMCH1 protein is regarded as a typical tumor suppressor due to its functions such as suppressing cells migration and promoting expression of p53. Actually, in lung (Zhang et al, 2019;Cao et al, 2021) and renal (https://www.proteinatlas.org/ENSG00000064042-LIMCH1/pathology/renal+cancer) carcinoma, it has been shown that LIMCH1 protein expression can be a favorable prognostic factor. However, the clinical and prognostic value of LIMCH1 protein expression in breast cancer is not enough explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also shown that LIMCH1 protein is a transcription factor that promotes the expression of p53 LIMCH1 protein is regarded as a typical tumor suppressor due to its functions such as suppressing cells migration and promoting expression of p53. Actually, in lung (Zhang et al, 2019;Cao et al, 2021) and renal (https://www.proteinatlas.org/ENSG00000064042-LIMCH1/pathology/renal+cancer) carcinoma, it has been shown that LIMCH1 protein expression can be a favorable prognostic factor. However, the clinical and prognostic value of LIMCH1 protein expression in breast cancer is not enough explored.…”
Section: Discussionmentioning
confidence: 99%
“…LIMCH1 protein regulates the activity of non-muscle myosin type 2A (NMIIA). It also promotes retrograde actin flow in lamellipodia and increases the strength of focal adhesion, preventing cell migration and increasing cell adhesion (Lin et al, 2017) described as a favorable prognostic factor in lung (Zhang et al, 2019;Cao et al, 2021) and renal cancers (https:// www.proteinatlas.org/ENSG00000064042-LIMCH1/ pathology/renal+cancer). However, its role in breast cancer remains unexplored.…”
Section: Limch1 As a New Potential Metastasis Predictor In Breast Cancermentioning
confidence: 99%
“…LIMCH1 has been identified as a key regulator of actin-cytoskeleton remodelling, involved in cell migration [ 22 ]. Due to its role in cell migration and adhesion, LIMCH1 has been associated with worse prognosis in multiple forms of cancer [ 33 ]. While LIMCH1 has not been directly associated with nerve function, actin-cytoskeletal frameworks are critical in neuronal development, and axonal growth and actin-binding LIM domain proteins are important in axonal regeneration [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of LIMCH1 led to disrupted focal adhesions and a subsequent increase in cell migration 21 . Several reports have linked LIMCH1 depletion to cancer progression suggesting reduced LIMCH1 levels may serve as a biomarker for tumor growth and/or metastasis in lung, breast and cervical cancers [22][23][24][25][26][27] . Beyond the role of LIMCH1 in focal adhesion formation and cell migration in vitro, nothing is known about its role in tissue-specific development or physiology.…”
Section: Introductionmentioning
confidence: 99%
“…25 and 400 ms, respectively, were used to assess contractile properties of the muscle with current passing through two platinum electrodes (PanLab LE 12406, Harvard Apparatus).Kinetics, force-frequency, fatigue, and recovery from fatigue protocols were collected and analyzed in LabChart 8 (ADInstruements) with the Peak Analysis module. Forcefrequency was tested by stimulating the muscle at 1 Hz, 5 Hz, 10 Hz, 20 Hz, 40 Hz, 60 Hz, 80 Hz, 120 Hz, 150 Hz and 200 Hz with one minute intervals between each frequency tested.…”
mentioning
confidence: 99%